Competence Of Mothers and Cadres in Early Detection Of Stunting in 3 Provinces in Indonesia - Muhasidah Muhasidah; Hartati Hartati; Baharuddin Baharuddin; Azizah Saleh (Direktorat Politeknik Kesehatan Makassar, 2025)
Stunting can affect a child's growth and development, leading to low human resource quality, thus posing a risk to work productivity. The stunting rate has increased significantly over the past 10 years, particularly in Eastern Indonesia, requiring serious attention from various professions, particularly the government, in collaboration with health workers. Research Objectives: 1) To identify the understanding, attitudes, and skills of mothers and health workers regarding the recognition, early detection, and risk factors of stunting, 2) increasing the knowledge of mothers and health cadres about early detection of stunting from the womb to the first 1000 days of life, and 3) To design an effective and practical guidebook that mothers and health workers can use to identify, early detection, and risk factors for stunting in the first 1,000 lives. Methods: This quantitative research study used a descriptive analytical design using a